Morphometric analysis of Willis circle arteries - Alma Voljevica; Elvira Talovic; Esad Pepic; Amna Pleho Kapic (Archives of Global Professionals, 2013)
Introduction: Willis arterial circle (circulus arteriosus cerebri Willisi) is the most important part of the collateral circulatory system of the brain. It functions in normal and pathological situations such as valvular mechanism and thus allows optimal blood supply of all parts of the brain tissue, which reduces the risk of transient ischemic attack (TIA) and stroke. The main pre-requisite for the normal function of the circle is its completeness and the lack of hypoplastic vessels. Materials and Methods: In this research, we used 100 angiograms of carotid system shown by serial angiography by Seldinger taken from the archives of the Department of Radiology, Clinical Center University of Sarajevo. For morphometric analysis of blood vessels, we used specially designed software program ELLIPSE (ViDiTo, Zoltan Tomoris, Kosice, Slovak Republic, tomori@saske.sk. In this way, it was possible to more easily store and analyze angiograms that were used for morphometric analysis. Results: In our study, larger diameters of blood vessels in Willis circle were observed in the younger subjects compared to older except the diameter of the internal carotid artery, which was about 0.2 to 0.3 mm larger in the older subjects. In both age groups among males, we recorded larger diameters of the internal carotid artery and segment before the circle of the posterior cerebral artery in relation to the female population, while the rear communicating artery in females was 0.1 mm wider in diameter compared to men in category of younger respondents.